2015
DOI: 10.1007/s10815-015-0525-z
|View full text |Cite
|
Sign up to set email alerts
|

Birth of a healthy child after preimplantation genetic screening of embryos from sperm of a man with non-mosaic Down syndrome

Abstract: Purpose The purpose of this study is to present a case of healthy infant born after intracytoplasmic sperm injection-in vitro fertilization (ICSI-IVF) with preimplantation genetic screening (PGS) using sperm from a man with non-mosaic trisomy 21 and a literature review. Materials and methods A 26-year-old euploid female and 29-year-old male with non-mosaic trisomy 21 and male factor undergoing ICSI-IVF treatment for primary infertility with embryo biopsy for PGS with comprehensive chromosomal screening (CCS) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previously, only spontaneous pregnancies have been reported in literature-all fathered by men with DS and a normal sperm count. The most recently reported cases include men with DS who used ART (intracytoplasmic sperm injection, ICSI) [28] and, in some instances, pre-implantation genetic diagnosis (PGT-A) of the embryos. This strategy revealed that only 1 of the 13 tested embryos exhibited mosaic trisomy.…”
Section: Assisted Reproductive Technology and Dsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, only spontaneous pregnancies have been reported in literature-all fathered by men with DS and a normal sperm count. The most recently reported cases include men with DS who used ART (intracytoplasmic sperm injection, ICSI) [28] and, in some instances, pre-implantation genetic diagnosis (PGT-A) of the embryos. This strategy revealed that only 1 of the 13 tested embryos exhibited mosaic trisomy.…”
Section: Assisted Reproductive Technology and Dsmentioning
confidence: 99%
“…In addition to questions related to the impact of intellectual disability and early dementia on parenting, another significant risk for individuals with DS would be the transmission of the pathology to their offspring. According to the literature data, all the children fathered by a man with DS (with or without ART) have been healthy [28]. In contrast, one out of three children born to a woman with DS themselves have DS [29].…”
Section: The Chromosomal Riskmentioning
confidence: 99%
“…Despite evidence of normal sexual development, there remain fewer than 50 cases of documented fertility in women with Down syndrome and four reported cases in non-mosaic males, one of whom achieved a pregnancy following preimplantation genetic screening (Aghajanova et al 2015). Potential contributors to infertility may be hormonal abnormalities, gonadal malformations, and psychological and social factors.…”
Section: Endocrinologicmentioning
confidence: 99%
“…Currently, infertility due to chromosomal abnormalities, with the corresponding pathologies of spermatogenesis, is overcome by reproductive technologies, and, paradoxically, it is possible that it is in male HT carriers with infertility that there is a chance to have a healthy offspring. For example, encouraging results were obtained using reproductive technologies for the production of healthy children from male carriers of trisomy 21 [71,72].…”
Section: Problems Of Reproduction In Carriers Of Htmentioning
confidence: 99%